Sources of the development of the ideas of aesthetic education of the personality in history of native scientific thought - Lytvynenko, S. V. (Problems of Engineer-Pedagogical Education, 2018)
The present article deals with the scientific views of a problem of aesthetic education of the personality in history of native scientific thought. The scientists of the past centuries considered aesthetic education to be a goal-oriented process of formation of creative personality who is able to perceive, to feel, to estimate the beautiful and create artistic values. On the assumption of the present article we can conclude that native scientists placed high emphasis on the problem of aesthetic education development in the course of any stage of human development. At different stages of history its content acquired its specific character that was conditioned on the reality of a definite historical period. Ideas that were recited reflected in further history of aesthetic education development. Aesthetic education plays an important role in education of highly educated, cultivated, humane and moral people. Aesthetic education provides for a сcomprehensive approach to the development of a personality, his or her aesthetic, creative and moral qualities that become apparent in his or her relation with other people, education, work, self-actualization, art and everyday life. Efficiently organized aesthetic education allows eliciting creative and mental potential, discerning native and foreign culture and provides an opportunity to achieve harmony in personal educational development and development of personal aesthetic values and views.